Complementary Therapies Used Among Adult Patients with Type 2 Diabetes Mellitus in Aceh, Indonesia - Niswah, Niswah; T, Chinnawong; J, Manasurakarn (Department of Nursing, Faculty of Medicine, Diponegoro University, 2014)
Purpose: This study aimed to reveal Complementary Therapies (CT) use among adult patients with type 2 diabetes mellitus (T2DM) in Aceh, Indonesia, and to determine the reasons of using the CT.Methods: A descriptive, cross-sectional study was undertaken using a self-reported questionnaire. One hundred and fifty four adult patients with T2DM has been completed the questionnaire. Descriptive statistics was used to analyze the data.Results: Herbs as a part of biological based therapies were the most popular of CT use among subjects in this study (100%) followed by mind-body intervention (94.2%), manipulation and body based methods (19.5%) and alternative medical methods (3.9%). The reasons for using each CT based on the belief in effects of CT on lowering blood sugar (100%), maintaining healthy body (76.6%), and relieving symptoms of DM (35.7%). Relatives and friends (98.7%) were main resources to obtain the CT information, and the family members (91.0%) were main support of CT use. While, the nature (89.0%) was the easiest source to access a CT product, followed by local markets (36.4%).Conclusion: This study found that herbs were believed by all subjects could reducing blood glucose, maintaining healthy body, and relieving symptoms of DM. Family members and easy to access the CT products from nature took the important role in influencing a person to use CT. More experimental studies examining effects of each CT especially herbal medicine and mind-body intervention are needed in the future.